To transform the equation −2y = 14 − 6x to slope-intercept form, we need to isolate y on one side of the equation.
Starting with −2y = 14 − 6x, we can divide both sides of the equation by -2 to solve for y:
-2y/-2 = (14 - 6x)/-2
y = -7 + 3x
Therefore, the equation is now in slope-intercept form: y = 3x - 7.
Transform the linear equation −2y=14−6x to slope-intercept form
15 answers
Write 0.4x+0.2y=0.6 in slope-intercept form.
To write the equation 0.4x + 0.2y = 0.6 in slope-intercept form, we need to isolate y on one side of the equation.
Starting with 0.4x + 0.2y = 0.6, we can subtract 0.4x from both sides of the equation:
0.2y = -0.4x + 0.6
Next, we can divide both sides of the equation by 0.2 to solve for y:
y = (-0.4/0.2)x + 0.6/0.2
Simplifying further, we have:
y = -2x + 3
Therefore, the equation is now in slope-intercept form: y = -2x + 3.
Starting with 0.4x + 0.2y = 0.6, we can subtract 0.4x from both sides of the equation:
0.2y = -0.4x + 0.6
Next, we can divide both sides of the equation by 0.2 to solve for y:
y = (-0.4/0.2)x + 0.6/0.2
Simplifying further, we have:
y = -2x + 3
Therefore, the equation is now in slope-intercept form: y = -2x + 3.
Write the linear equation 3y=6x−18 in slope-intercept form.
To write the equation 3y = 6x - 18 in slope-intercept form, we need to isolate y on one side of the equation.
Starting with 3y = 6x - 18, we can divide both sides of the equation by 3 to solve for y:
3y/3 = (6x - 18)/3
y = 2x - 6
Therefore, the equation is now in slope-intercept form: y = 2x - 6.
Starting with 3y = 6x - 18, we can divide both sides of the equation by 3 to solve for y:
3y/3 = (6x - 18)/3
y = 2x - 6
Therefore, the equation is now in slope-intercept form: y = 2x - 6.
What is the slope and the y-intercept of the equation 9+272x=−32y. Write the y-intercept as an ordered pair.(1 point)
The slope is . The y-intercept is ( ).
The slope is . The y-intercept is ( ).
To determine the slope and y-intercept of the equation 9 + 272x = -32y, we need to rewrite the equation in slope-intercept form, y = mx + b.
Starting with 9 + 272x = -32y, we can first divide both sides of the equation by -32 to isolate y:
(9 + 272x)/(-32) = y
Simplifying further, we have:
y = -8.5x - 0.28125
Therefore, the slope of the equation is -8.5 and the y-intercept is (-0.28125).
Starting with 9 + 272x = -32y, we can first divide both sides of the equation by -32 to isolate y:
(9 + 272x)/(-32) = y
Simplifying further, we have:
y = -8.5x - 0.28125
Therefore, the slope of the equation is -8.5 and the y-intercept is (-0.28125).
What is the slope and the y-intercept of the equation 9+27/2x=−3/2y. Write the y-intercept as an ordered pair.(1 point)
The slope is . The y-intercept is ( ).
The slope is . The y-intercept is ( ).
To determine the slope and y-intercept of the equation 9 + 27/2x = -3/2y, we need to rewrite the equation in slope-intercept form, y = mx + b.
Starting with the equation 9 + 27/2x = -3/2y, we can first divide both sides of the equation by -3/2 to isolate y:
(9 + 27/2x) / (-3/2) = y
Simplifying further, we have:
y = -18 - 9x/2
Therefore, the slope of the equation is -9/2 and the y-intercept is (-18, 0).
Starting with the equation 9 + 27/2x = -3/2y, we can first divide both sides of the equation by -3/2 to isolate y:
(9 + 27/2x) / (-3/2) = y
Simplifying further, we have:
y = -18 - 9x/2
Therefore, the slope of the equation is -9/2 and the y-intercept is (-18, 0).
incorrect
My apologies for the incorrect response. Let's calculate the slope and y-intercept correctly for the equation 9 + 27/2x = -3/2y.
We'll begin by isolating y on one side of the equation:
9 + 27/2x = -3/2y
To isolate y, we can multiply both sides by -2/3:
(-2/3)(9 + 27/2x) = y
Simplifying, we have:
-2(9 + 27/2x)/3 = y
-6 - 18x/3 = y
-2 - 6x = y
Now the equation is in the form y = mx + b, where m is the slope and b is the y-intercept.
From the equation y = -2 - 6x, we can see that the slope is -6 and the y-intercept is -2.
Therefore, the slope of the equation is -6, and the y-intercept is (-2).
We'll begin by isolating y on one side of the equation:
9 + 27/2x = -3/2y
To isolate y, we can multiply both sides by -2/3:
(-2/3)(9 + 27/2x) = y
Simplifying, we have:
-2(9 + 27/2x)/3 = y
-6 - 18x/3 = y
-2 - 6x = y
Now the equation is in the form y = mx + b, where m is the slope and b is the y-intercept.
From the equation y = -2 - 6x, we can see that the slope is -6 and the y-intercept is -2.
Therefore, the slope of the equation is -6, and the y-intercept is (-2).
incorecct
Apologies for the repeated error. Let's correctly determine the slope and y-intercept for the equation 9 + 27/2x = -3/2y.
First, let's rearrange the equation to isolate y:
9 + 27/2x = -3/2y
Multiply both sides by -2/3 to solve for y:
(-2/3)(9 + 27/2x) = y
-6 - 18x/3 = y
-2 - 6x = y
Now the equation is in the form y = mx + b, where m represents the slope and b represents the y-intercept.
Comparing the equation y = -2 - 6x, we can determine that the slope is -6 and the y-intercept is -2.
Therefore, the slope of the equation is -6, and the y-intercept is (-2, 0).
First, let's rearrange the equation to isolate y:
9 + 27/2x = -3/2y
Multiply both sides by -2/3 to solve for y:
(-2/3)(9 + 27/2x) = y
-6 - 18x/3 = y
-2 - 6x = y
Now the equation is in the form y = mx + b, where m represents the slope and b represents the y-intercept.
Comparing the equation y = -2 - 6x, we can determine that the slope is -6 and the y-intercept is -2.
Therefore, the slope of the equation is -6, and the y-intercept is (-2, 0).
not right
Apologies for the continued confusion. Let's correct the calculation for the slope and y-intercept of the equation 9 + 27/2x = -3/2y.
First, let's rearrange the equation to isolate y:
9 + 27/2x = -3/2y
To isolate y, we can multiply both sides of the equation by -2/3:
(-2/3)(9 + 27/2x) = y
Simplifying, we have:
-6 - 18x/3 = y
-6 - 6x = y
Now we have the equation in the form y = mx + b, where m is the slope and b is the y-intercept.
Comparing the equation y = -6 - 6x, we can determine that the slope is -6 and the y-intercept is -6.
Therefore, the slope of the equation is -6, and the y-intercept is (0, -6).
First, let's rearrange the equation to isolate y:
9 + 27/2x = -3/2y
To isolate y, we can multiply both sides of the equation by -2/3:
(-2/3)(9 + 27/2x) = y
Simplifying, we have:
-6 - 18x/3 = y
-6 - 6x = y
Now we have the equation in the form y = mx + b, where m is the slope and b is the y-intercept.
Comparing the equation y = -6 - 6x, we can determine that the slope is -6 and the y-intercept is -6.
Therefore, the slope of the equation is -6, and the y-intercept is (0, -6).